Hypertriglyceridemia: rationale, design and implementation of the Australian Hypertriglyceridemia Registry. Issue 2 (21st April 2022) - Pang, Jing; Li, Stephen C.H.; Chan, Dick C.; Sullivan, David R.; Woodward, Ann-Marie; Watts, Gerald F.
Abstract : Purpose of review: Hypertriglyceridemia (HTG) is a risk factor for atherosclerotic cardiovascular disease (ASCVD), aortic stenosis, hepatic steatosis and pancreatitis. We briefly review the aetiology and treatment of HTG and familial chylomicronemia syndrome (FCS), as well as the implementation of a clinical quality registry for improving care, the Australian Hypertriglyceridemia (AUSTRIG) Registry. Recent findings: There is a need to improve the detection of individuals with severe HTG and FCS, who could benefit from more intense and novel treatments to prevent end-organ damage. Patient registries provide valuable data for advancing care of individuals with severe HTG at high risk of acute pancreatitis, steatohepatitis and ASCVD. However, there is a paucity of registries of such patients. We outline the design and implementation of the AUSTRIG Registry. Summary: Clinical registries can be employed in many ways for improving outcomes for patients with HTG, through the collation and analysis of data for enabling health service planning, clinical trials and audits, and for better informing and empowering registrants.